An aesthetics of law and culture text, images, screens - Law and Literature Association of Australia. International Conference 2002 : University of Melbourne Law School); Kenyon, Andrew T.; Rush, Peter, 1959- (Amsterdam ; London : Elsevier JAI, 2004)
This special volume of "Studies in Law, Politics, and Society - The Aesthetics of Law and Culture: Texts, Images, Screens" - examines practices of representation and their relation to juridical and cultural formations. The chapters range across the media of speech and writing, word and image, legislation and judgment, literature, cinema and photography. The contributions draw on disciplines including jurisprudence, literary criticism, philosophy, cinema studies, art and visual studies, cartography, historiography and medicine. They are ordered according to four prominent themes in contemporary, theoretically informed critical scholarship: Crime Scenes: Sexuality and Representation; Sites Unsaid: Testimony, Image, Genre; (Post) Colonial Appropriations; and Screen Culture: Sovereignty, Cinema and Law.
Alter egos : the mise-en-scène of law and aesthetics / Peter D. Rush and Andrew T. Kenyon. Crime scenes : sexuality and representation. Exhibiting the hymen : the blank page between law and literature / Nina Philadelphoff-Puren -- "It forced me to open more than I could bear" : H.A.D., paedophilia, and the discursive limits of the male heterosexual body / Ben Golder -- Arresting images/fugitive testimony : the resistant photography of Evergon / Derek Dalton. Sites unsaid : testimony, image, genre. The trial : elements of a legal assemblage of desire / Edward Mussawir -- Character evidence and the literature of the Theophrastan character : a phenomenology of testimony / Michael FitzGerald -- Injury as melodrama / Samantha Hardy -- Graven images : "The Hart Island Project" / Rebecca Scott Bray. (Post)colonial appropriations. Awash in a tide of history : "responsibility" for cultural violence--A comparative analysis of Nulyrimma and Voss / Lee Godden -- Cartography, property and the aesthetics of place : mapping native title in Australia / Alexander Reilly -- gods and humans / Nasser Hussain. Screen culture : sovereignty, cinema and law. Unworking death in "Unforgiven" : law, ethos, violence / Thomas L. Dumm -- Sovereign contempt / Peter J. Hutchings -- One Recht to rule them all! Law's empire in the age of empire / William MacNeil.
"Almost all the chapters in this book emerged from the 11th International Conference of the Law and Literature Association of Australia"--Pref.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Law and aesthetics -- Congresses; Culture and law -- Congresses; Law & society; Social Science -- Sociology -- General; Law -- General